The effect of a single nucleotide polymorphismof the CYP4F2 gene on blood pressure and 20-hydroxyeicosatetraenoic acidexcretion after weight loss - Ward, Natalie; Croft, K.; Puddey, I.; Phillips, M.; van Bockxmeer, F.; Beilin, L.; Barden, A. (2014)
Background: Genetic background partly determines the efficacy of interventions to lower blood pressure (BP). The CYP4F2 and CYP4A11 enzymes are renal 20-hydroxyeicosatetraenoic acid (20-HETE) synthases that regulate BP. Gene variants of CYP4F2 and CYP4A11 associate with hypertension and stroke. We showed that a gene variant of CYP4F2 but not CYP4A11 was associated with increased 20-HETE excretion and BP. Aim: To compare BP and 20-HETE responses in carriers of the CYP4F2 1347G/A polymorphism and controls CYP4F2-GG (wildtype), during weight loss. Methods: Volunteers genotyped as CYP4F2GA/AA (n = 26) and controls genotyped as CYP4F2 GG (n  = 27) were counselled to reduce weight for 12 weeks, followed by 4 weeks of weight stabilization. Weight, 24-h BP, pulse pressure and urinary 20-HETE were measured at baseline, 12 and 16 weeks. Results: At baseline, SBP was (+1.7 mmHg, P = 0.047) in the CYP4F2 GA/AA genotype. Compared with baseline, weight fell by 3.9 kg, P = 0.0001, in both genotypes, and was maintained to 16 weeks. SBP fell by (−7.6 mmHg, P = 0.004) in both genotypes after 12 weeks. However, after weight stabilization, SBP was +3.6 mmHg, P = 0.004 in CYP4F2 GA/AA genotype. DBP and heart rate changed similarly over time. Pulse pressure fell with weight loss (P < 0.001), but was elevated in the CYP4F2 GA/AA genotype at all time-points (+3.1 mmHg, P < 0.001). Urinary 20-HETE was similar at baseline and 12 weeks but elevated in the CYP4F2 GA/AA genotype (P = 0.017) after weight stabilization. Conclusion: Maintenance of lower BP after weight loss is more difficult for carriers of the CYP4F2 G1347A polymorphism and may be related to increased arterial stiffness and increased 20-HETE synthesis.